Anarchism Paul Karl Feyerabend: His Concept and Dedication to Development of Contemporary Islamic Education - Pridar, Ahmad Ashshiddiqie; Sabarudin, Sabarudin (Edumaspul: Jurnal Pendidikan, 2023)
Education is a basic and very important activity for every individual. Through education, humans can gain knowledge about everything. Apart from that, education also influences human awareness in knowing God more deeply and understanding themselves. Therefore, quality education will provide the expected results, namely the use of an individual’s intellectual abilities in all aspects of his life. Paul Karl Feyerabend is known as a controversial philosopher who put forward anarchist views in epistemology and scientific methodology. In the context of Islamic education, Feyerabend believes that freedom of thought, criticism and dialogue are important principles that must be emphasized in the learning process. The purpose of this research is to investigate the concept and dedication of Paul Karl Feyerabend in the context of contemporary Islamic education with an anarchist perspective. This research is library research with a qualitative approach that focuses on descriptive analysis based on data information obtained, including sources. primary or secondary. The results of the analysis show that in Feyerabend’s view, the concept of anarchism is not about disorder or chaos, but rather about diversity, plurality, and criticism of authority and norms that inhibit freedom of thought and expression. Feyerabend’s dedication to contemporary Islamic education can be seen in his efforts to promote freedom of thought, independent research and as a source of inspiration for developing alternative approaches to religious learning. The anything goes principle provides the basis for creating an educational environment that is inclusive, critical, and based on freedom of thought.